Effectiveness of Xin Jia Xuan Bai Cheng Qi Decoction in treating acute exacerbation of chronic obstructive pulmonary disease: study protocol for a multicentre, randomised, controlled trial - Yan Zhang; Jing Zhang; Jin Jin; Hongchun Zhang; Demin Li; Yue Jing; Tianhong Cui; Xiang Lei; Qijian Cheng; Erran Li (BMJ Open)
Introduction Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) brings a serious impact on patients’ quality of life, and has extremely high morbidity and mortality worldwide. Although there are many therapies being developed to alleviate symptoms and reduce mortality, a few studies have supported which treatment method is the best. Traditional Chinese medicine (TCM) has shown good potential in the prevention and treatment of AECOPD, especially in terms of supplementation and reduction of dosage and adverse effect of Western medicine. The purpose of this study is to compare the effectiveness of combination of TCM and Western medicine with conventional therapy alone for AECOPD, and to ensure whether the combined therapy may reduce the use of systemic glucocorticoid in AECOPD without influencing efficacy.Methods and analysis A multicentre, randomised, double-blind, placebo-controlled study was conducted to enrol a total of 360 eligible patients who will be randomised into integrated Chinese and Western medicine group A, B and Western standard Medicine group C. After 5 days of intervention and 1 month of follow-up, the efficacy and safety of Xin Jia Xuan Bai Cheng Qi Decoction in patients with AECOPD will be observed. The results of evaluation indicators include: clinical symptoms, biochemical indicators such as blood gas analysis, inflammatory markers, hospitalisation time, TCM syndrome evaluation, biological indicators such as airway, intestinal flora sequencing.Ethics and dissemination This trail has been approved by the Ethics Committee of China-Japan Friendship Hospital. The results will be disseminated in international peer-reviewed journals and be presented in academic conferences. The results will also be disseminated to patients by telephone, inquiring on patient’s poststudy health status during the follow-up.Trial registration number ChiCTR1800016915